TEACHING ENGLISH THROUGH AN ONLINE LEARNING MODEL TO EFL STUDENTS IN RURAL AREAS DURING THE COVID-19 PANDEMIC: TEACHER'S REFLECTION - Dina Fitriana; Nia Purnamasari (English Education Department of STKIP Pasundan, 2021)
Theoretical and empirical grounds suggest that the discussions on teaching English through an online learning system to EFL students in rural areas are limited in numbers. The voices and challenges experienced by EFL teachers of rural areas remain unexplored. This research is thus to shed light on the difficulties of EFL teachers in teaching English through an online learning system to EFL students of rural areas during the COVID-19 pandemic. This research used a qualitative research method with a case study design. The research participant was a teacher teaching English at one of the senior high schools in rural area in West Java. The data collection techniques used in this research were reflective writing journals and semi-structured interviews. Three steps were used in analyzing the data: data condensation, data display, drawing, and verifying conclusion. The findings revealed two primary challenges the EFL teacher faces during online learning: technological challenges and students' self-regulated learning. Technical challenges related to an unstable internet connection, limited internet quota, and lack of appropriate devices. Meanwhile, students' self-regulated learning is related to students' motivation in online learning. Several possible suggestions were applied in facing the challenges in online education: creativity, using different methods, and learning strategies appropriate to the teaching material.